Sekolah Berasrama; Penjaminan Mutu dan Implementasi - Sulhan Hamid H Lubis; Sri Milfayetti; Saut Purba; Eka Daryanto (Departement of Mathematics Education, 2023)
Data obtained from dapodik as many as 934 high schools throughout Indonesia that provide education with dormitory services. The proliferation of boarding schools is inseparable from the quality of education provided by the school. Until today, there is no quality standard for boarding schools because each school has its own peculiarities / characteristics and is no exception at SMAN 2 Plus Panyabungan mandailing Natal regency, North Sumatra. In this study using qualitative descriptive method. Data collection using documentation and literature techniques. Data analysis goes through several stages, namely data reduction, display data, and conclusion/verification. The results of this study show that: 1) The mapping of the quality of education carried out by boarding schools varies greatly but still refers to the National Education Standards; 2) Making a quality improvement plan as outlined in the School Work Plan in accordance with the excellence of boarding schools; 3) Implementation of quality fulfillment both in school management and the learning process in boarding schools using the government curriculum and parenting curriculum; 4) Monitoring and evaluating the process of implementing quality fulfillment in terms of the characteristics of boarding schools; 5) Setting new standards and developing quality improvement strategies based on the results of monitoring and evaluation.